Kandungan Fosfor dan Hasil Tanaman Jagung Pada Ultisol Akibat Pemberian Biochar Dan Pupuk Kandang - Lumbanraja, Parlindungan; Nababan, Mika Lidia; Siagian, Irwan; Limbong, Benjamin Surya (Agriculture Faculty of Flores University, 2024)
Ultisol is a type of soil that is not very fertile but is commonly used for agriculture. The research aimed to gather information about how the application of rice husk biochar and cow manure, either separately or combined, would affect soil phosphorus levels, the uptake of phosphorus by spring corn plants (Zea mays saccaratha L.), and the weight of the plants when they are wet and when they are dried. The study used a 4x3 Factorial Randomized Block Design, with four levels of biochar and three levels of cow manure, followed by an analysis of variance. The research location is situated at an altitude of around 33 meters above sea level (masl) with soil acidity (pH) ranging from 5.5 to 6.5, and characterized by Ultisol soil type. The parameters observed included soil phosphorus levels, phosphorus uptake by plant stems and leaves, wet weight and oven-dried weight of plant stems and leaves, and wet weight of harvested cobs. The results of the study showed that applying rice husk biochar and manure as single treatments did not have a significant effect on increasing soil phosphorus availability, plant phosphorus uptake, wet weight and dry weight of plant stems and leaves, or baby corn production. However, there was a tendency for each observation parameter to show some improvement